Anaerobic metabolic responses of sludge and mine wastewater-derived consortia to winery wastewater-related compounds - Ana Baía; Alonso I. Arroyo-Escoto; Nuno Ramos; César Afonso; Gaetano R. Pesce; Maria C. Fernandes; Annabel Fernandes (World Journal of Microbiology and Biotechnology, 2026)
Winery wastewater contains readily biodegradable organic matter, but some of its components can inhibit anaerobic microbial activity. This study compares two enriched microbial consortia, derived from anaerobic digester sludge (ADS) and mining-process wastewater (MPW), exposed to alcohols, carboxylic acids, and phenolics. Assays were conducted in acetate–fumarate-based media containing low or high concentrations of each compound class and a combined condition containing the compounds at their highest levels. Growth, fumarate consumption, succinate production, acetate turnover, and compound consumption were monitored. Full-length 16 S rRNA gene sequencing showed that ADS was dominated by Proteus (56.9%) and Escherichia (28.6%). MPW showed a more even profile dominated by Proteus (35.8%), Wolinella (32.9%), and Escherichia (23.0%). Under control conditions, MPW showed higher growth (0.284 vs. 0.181 h −1 ) and succinate production rates (0.171 vs. 0.106 g L −1 h −1 ) than ADS. Alcohols caused little change in fumarate consumption, but high carboxylic acid concentrations reduced fumarate consumption rates to 0.115 and 0.162 g L −1 h −1 in ADS and MPW, respectively. Phenolics reduced the ADS succinate production rate to 0.059 g L −1 h −1 , while MPW remained near its control value (0.169 vs. 0.171 g L −1 h −1 ). Under combined exposure, ADS maintained fumarate consumption and increased succinate production from 0.106 to 0.157 g L −1 h −1 , but MPW decreased from 0.125 to 0.092 g L −1 h −1 . Both bacterial composition and the chemical conditions of exposure influenced anaerobic resilience. The combined use of taxonomic and metabolic indicators may therefore improve the selection of consortia for the biodegradation and valorization of complex agro-industrial wastewaters, including their integration into bioelectrochemical platforms.

Unravelling the role of organic ligands in Zn(II) diffusion and sorption mechanisms in compacted Na-illite - Xiaoyan Wei; Bin Ma; Martin A. Glaus; Luc R. Van Loon; Duoqiang Pan; Maria Marques Fernandes; Rainer Dähn; Wangsuo Wu; Sergey V. Churakov (Geochimica et Cosmochimica Acta, 2026)

Climate Predicts Tree Dispersal Strategies Across Brazil's Ecosystems - Fernanda C. Souza; Vinícius Andrade Maia; Renata Françoso; Matheus Coutinho Freitas de Oliveira; Ana Beatriz Ligo; Bruno X. Pinho; Jesús Aguirre‐Gutiérrez; Martin Sullivan; Larissa Rocha‐Santos; Laura de Brito Évora; Leonardo de Sousa Miranda; María Natalia Umaña; et al. (Global Ecology and Biogeography, 2026)
Aim We investigate the distribution of dispersal modes — endozoochory (via animal ingestion), synzoochory (via animal seed accumulation) and anemochory (via wind)—and seed mass of woody plants across Brazilian ecosystems, testing whether their relative abundance in local plant communities could be predicted by climate, edaphic factors and dispersal agents (e.g., the main vectors moving seeds). We expected climate to be the main predictor of dispersal strategy abundance. Location Brazilian ecosystems (Amazon, Atlantic Forest, Cerrado and Caatinga). Time Period 2004–2020. Major Taxa Studied Woody angiosperms, trees and shrubs. Methods We assigned seed mass to 1984 species and dispersal mode to 2203 species within 300 old‐growth and non‐flooded plots. We employed Random Forest regressions to assess the influence of water availability, temperature seasonality, soil fertility, wind and frugivorous primates on the community‐weighted means of seed mass and dispersal modes. We mapped predictions and estimated the area of applicability to identify regions where predictions were reliable. Results Climate was the main factor predicting tree dispersal strategies, followed by dispersal agents or soil properties. Endozoochory was prevalent in wetter regions with high water availability and greater diurnal temperature range. Anemochory was more common in drier regions with low water availability, stronger winds and greater diurnal temperature range, whereas synzoochory was more abundant in areas with low temperature seasonality. Heavier seeds were more prevalent in regions with less seasonal temperatures, smaller diurnal temperature ranges and weaker winds. Main Conclusions Climate is a key predictor of the distribution and prevalence of plants with contrasting dispersal modes and seed masses. We thus expect functional responses to environmental change associated with shifts in the relative abundance of dispersal strategies, with implications for ecosystem services. Our results also highlight the critical role of plot‐based datasets in improving our understanding of how environmental factors influence seed dispersal strategies across tropical ecosystems.

Dietary replacement of whole soybean grain with micronized defatted soybean meal in dairy cow diets: effects on intake, digestibility, ruminal parameters, and milk yield and composition - Thiago Thiarles Braw André Furlan R Maciel; Eliane Sayuri Miyagi Okada; Euclides Reuter De Oliveira; Jefferson Rodrigues Gandra; Vera Lúcia Banys; Thaís Da Silva Fernandes; Andréa Maria de Araújo Gabriel; Claudia Andrea Lima Cardoso; Vicente Ribeiro Rocha Júnior; Ranney Késia Oliveira de Jesus Silva; Flávio Pinto Monção (Tropical Animal Health and Production, 2026)
This study aimed to evaluate effects of replacing whole soybean grain with micronized defatted soybean meal (MDSM) in diets of lactating dairy cows on performance, digestion, metabolism, and milk yield and composition. Ten primiparous Jersey cows with an initial body weight (BW) of 410 ± 9 kg and 105 ± 5 days in milk were used. Five replacement levels (0, 25, 50, 75, and 100% of dietary DM) of whole soybean grain with MDSM were evaluated. The experiment was conducted as two simultaneous 5×5 Latin squares, each composed of five animals, five treatments, and five experimental periods, totaling 80 days. Each period lasted 16 days, including 12 days for adaptation and 4 days for data collection. No differences were observed among experimental diets for dry matter intake (mean = 14.58 kg day -1 ; p = 0.08) or organic matter intake (mean = 13.60 kg day -1 ; p = 0.08). Increasing dietary inclusion of MDSM resulted in greater crude protein intake, with the highest intake observed at 14% MDSM inclusion. A linear increase (P < 0.05) was observed in digestibility of dry matter, organic matter, crude protein, ether extract, and starch as MDSM inclusion increased. The inclusion level that maximized short-chain fatty acid production was 9.22%. Milk yield corrected to 3.5% fat increased linearly with increasing MDSM inclusion. Inclusion of MDSM did not affect milk fat (p = 0.41), protein (p = 0.86), or lactose (p = 0.88) concentrations. Complete replacement of whole soybean grain with MDSM in diets of Jersey cows increased milk yield, improved feed efficiency, and did not alter milk composition. Additionally, it enhanced digestibility of dry matter, organic matter, crude protein, and starch.

Compounded oral doxycycline in late-term pregnant mares: pharmacokinetics, fetoplacental diffusion, and neonatal safety - Fernanda T.D'el Rey Dantas; Igor F. Canisso; Lorena S. Feijó; Paula Maria Fernandes de Vasconcelos; Michel L. Campos; Alexander V. Ulanov; Zhong Li; Gino L.B.L. Pizzi; Carlos E.W. Nogueira; Bruna R. Curcio (Theriogenology, 2026)

Trees control hillslope subsurface flow: Insights from stemflow and throughfall experiments, geophysical surveys, and numerical modeling - Simone Di Prima; Gersende Fernandes; Maria Burguet; Maria Paz Salazar; Elisa Marras; Ilenia Murgia; Konstantinos Kaffas; Luca Peruzzo; Ryan D. Stewart; Majdi R. Abou Najm; Alessandro Comegna; Laurent Lassabatere; et al. (Journal of Hydrology, 2026)

Enantioselective toxicity of 3,4-methylenedioxypyrovalerone in Daphnia magna: Assessment of morphophysiological, behavioural, biochemical and reproductive responses - Ariana Pérez-Pereira; Ana R. Carvalho; Pedro A. Costa; Bruno B. Castro; João S. Carrola; Virgínia M.F. Gonçalves; Ana R.L. Ribeiro; Ana Sofia Almeida; Carla Fernandes; Maria E. Tiritan; Cláudia Ribeiro (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Soil–climate interactions drive above-ground biomass in the Caatinga, the largest Neotropical seasonally dry tropical forest - Alexandre T. Brunello; Domingos Cardoso; Peter W. Moonlight; Ítalo A. C. Coutinho; John Cunha; Mário M. do Espírito Santo; Magna S. B. de Moura; Luciano P. de Queiroz; Rubens M. dos Santos; Tiina Särkinen; Raquel C. Miatto; Tony C. de S. Oliveira; et al. (Plant and Soil, 2025)

Mobility of populations in the transition from Muslim world to Portuguese Kingdom in the Algarve, South Portugal, 11th-13th centuries - Anne-France Maurer; Rebecca MacRoberts; Judith Margarita López-Aceves; Alvaro Felipe Ortega-González; Claudia Relvado; Teresa Fernandes; Francisco Curate; João Teixeira; Xavier Roca-Rada; Bastien Llamas; Isabel Luzia; Alexandra Pires; et al. (Archaeological and Anthropological Sciences, 2025)

Foraminiferal palaeoecology of the Aptian/Albian deposits of the Romualdo Formation (Araripe Basin) in northeastern of Brazil - Rilda C. Araripe; David H. D. Oliveira; Marta C. Viviers; Renata Moura De Mello; Anne C. M. Brandão; Bruno Fernandes; Rizoaldo Barbosa; Anny R. de A. Carvalho; Jefferson Santos; Maria Emília T. R. Tomé; Flávia A. Pedrosa Lemos; Ludmila A. C. Do Prado; et al. (Palaeobiodiversity and Palaeoenvironments, 2025)

In-situ electrogeneration of H2O2 and hydroxyl radical applied for venlafaxine degradation: A novel strategy using FeSe2-modified carbon gas diffusion electrode - Fausto E. Bimbi Júnior; Oswaldo C. Junior; Robson S. Souto; João Pedro P. Encide; Micael M. Baruch; Maria C.V. Felipe; Larissa Fernandes; Isabela F. Araujo; Carlos H.M. Fernandes; Igor G.S. Oliveira; Kathia M. Honorio; Renata Colombo; et al. (Chemical Engineering Journal, 2025)

A global assessment of microplastic abundance and characteristics on marine turtle nesting beaches - Zara L.R. Botterell; Jed Ardren; Elly Dove; Ellen McArthur; David S. Addison; Oyeronke M. Adegbile; Pierre Didier Agamboue; Andrews Agyekumhene; Phil Allman; Alexandra Alterman; Adren Anderson; Theresa Arenholz; et al. (Marine Pollution Bulletin, 2025)

Effects of soybean molasses on ruminal fermentation pattern, performance and meat quality of feedlot sheep - Sérgio A.G. Pereira-Junior; Juliana A. Torrecilhas; Rayanne V. Costa; Edivilson S. Castro Filho; Maria Carolina G. Arruda; João Pedro A. Bertoco; Andresa L. Feliciano; Julia L. Rodrigues; Rosemary L. Galati; Angélica C. dos Santos; Marcos R. Chiaratti; Ricardo P. Nociti; et al. (Small Ruminant Research, 2025)

Enteroaggregative Escherichia coli (EAEC) isolates obtained from non-diarrheic children carry virulence factor-encoding genes from Extraintestinal Pathogenic E. Coli (ExPEC) - Bruna M. Luiz; Maria C. Cergole-Novella; Stéfani T. A. Dantas; Daiany R. P. de Lira; Guilherme F. R. de Souza; Iranildo do A. Fernandes; Henrique Orsi; Guilherme Solveira; Vera L. M. Rall; Luís F. dos Santos; Rodrigo T. Hernandes (Brazilian Journal of Microbiology, 2024)

Disentangling the veil line for Brazilian biodiversity: An overview from two long-term research programs reveals huge gaps in ecological data reporting - Aretha Franklin Guimaraes; Luciano Carramaschi de Alagao Querido; Taina Rocha; Domingos de Jesus Rodrigues; Pedro Lage Viana; Helena de Godoy Bergallo; Geraldo Wilson Fernandes; Tiago Shizen Pacheco Toma; Helena Streit; Gerhard Ernst Overbeck; Alberico Queiroz Salgueiro de Souza; Albertina Pimentel Lima; et al. (Science of The Total Environment, 2024)

The ADnet Bayesian belief network for alder decline: Integrating empirical data and expert knowledge - Inês Gomes Marques; Cristina Vieites-Blanco; Patricia M. Rodríguez-González; Pedro Segurado; Marlene Marques; Maria J. Barrento; Maria R. Fernandes; Arthur Cupertino; Helena Almeida; Idoia Biurrun; Tamara Corcobado; Filipe Costa e Silva; et al. (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Photodynamic activation of phytochemical-antibiotic combinations for combatting Staphylococcus aureus from acute wound infections - Ariana S.C. Gonçalves; Miguel M. Leitão; José R. Fernandes; Maria José Saavedra; Cristiana Pereira; Manuel Simões; Anabela Borges (Journal of Photochemistry and Photobiology B: Biology, 2024)

Acquisition of elemental sulfur by sulfur‐oxidising Sulfolobales - Maria C. Fernandes‐Martins; Carli Springer; Daniel R. Colman; Eric S. Boyd (Environmental Microbiology, 2024)
Elemental sulfur (S 8 0 )‐oxidising Sulfolobales (Archaea) dominate high‐temperature acidic hot springs (>80°C, pH 8 0 ‐oxidising members of the Sulfolobales reveal a patchy distribution of genes encoding sulfur oxygenase reductase (SOR), an S 8 0 disproportionating enzyme attributed to S 8 0 oxidation. Here, we report the S 8 0 ‐dependent growth of two Sulfolobales strains previously isolated from acidic hot springs in Yellowstone National Park, one of which associated with bulk S 8 0 during growth and one that did not. The genomes of each strain encoded different sulfur metabolism enzymes, with only one encoding SOR. Dialysis membrane experiments showed that direct contact is not required for S 8 0 oxidation in the SOR‐encoding strain. This is attributed to the generation of hydrogen sulfide (H 2 S) from S 8 0 disproportionation that can diffuse out of the cell to solubilise bulk S 8 0 to form soluble polysulfides (S x 2− ) and/or S 8 0 nanoparticles that readily diffuse across dialysis membranes. The Sulfolobales strain lacking SOR required direct contact to oxidise S 8 0 , which could be overcome by the addition of H 2 S. High concentrations of S 8 0 inhibited the growth of both strains. These results implicate alternative strategies to acquire and metabolise sulfur in Sulfolobales and have implications for their distribution and ecology in their hot spring habitats.

Turning discarded blue shark (Prionace glauca) skin into a valuable nutraceutical resource: An enzymatic collagen hydrolysate - Ezequiel R. Coscueta; Nádia Cunha Fernandes; María Emilia Brassesco; Ana Rosa; André Almeida; Maria Manuela Pintado (Food Bioscience, 2024)

A global initiative for ecological and evolutionary hologenomics - Aoife Leonard; Javier Abalos; Titus Adhola; Windsor Aguirre; Ostaizka Aizpurua; Shahzad Ali; Franco Andreone; Fabien Aubret; Hefer D. Ávila-Palma; Lizbeth Fabiola Bautista Alcantara; Juan F. Beltrán; Rachel Berg; et al. (Trends in Ecology & Evolution, 2024)

Reading tea leaves worldwide: Decoupled drivers of initial litter decomposition mass‐loss rate and stabilization - Judith M. Sarneel; Mariet M. Hefting; Taru Sandén; Johan van den Hoogen; Devin Routh; Bhupendra S. Adhikari; Juha M. Alatalo; Alla Aleksanyan; Inge H. J. Althuizen; Mohammed H. S. A. Alsafran; Jeff W. Atkins; Laurent Augusto; et al. (Ecology Letters, 2024)
The breakdown of plant material fuels soil functioning and biodiversity. Currently, process understanding of global decomposition patterns and the drivers of such patterns are hampered by the lack of coherent large‐scale datasets. We buried 36,000 individual litterbags (tea bags) worldwide and found an overall negative correlation between initial mass‐loss rates and stabilization factors of plant‐derived carbon, using the Tea Bag Index (TBI). The stabilization factor quantifies the degree to which easy‐to‐degrade components accumulate during early‐stage decomposition (e.g. by environmental limitations). However, agriculture and an interaction between moisture and temperature led to a decoupling between initial mass‐loss rates and stabilization, notably in colder locations. Using TBI improved mass‐loss estimates of natural litter compared to models that ignored stabilization. Ignoring the transformation of dead plant material to more recalcitrant substances during early‐stage decomposition, and the environmental control of this transformation, could overestimate carbon losses during early decomposition in carbon cycle models.

Camera trap surveys of A tlantic F orest mammals: A data set for analyses considering imperfect detection (2004–2020) - Ingridi Camboim Franceschi; Rubem Augusto da Paixão Dornas; Isabel Salgueiro Lermen; Artur Vicente Pfeifer Coelho; Ademir Henrique Vilas Boas; Adriano Garcia Chiarello; Adriano Pereira Paglia; Agnis Cristiane de Souza; Alana Rafaela Borsekowsky; Alessandro Rocha; Alex Bager; Alexander Zaidan de Souza; et al. (Ecology, 2024)
Camera traps became the main observational method of a myriad of species over large areas. Data sets from camera traps can be used to describe the patterns and monitor the occupancy, abundance, and richness of wildlife, essential information for conservation in times of rapid climate and land‐cover changes. Habitat loss and poaching are responsible for historical population losses of mammals in the Atlantic Forest biodiversity hotspot, especially for medium to large‐sized species. Here we present a data set from camera trap surveys of medium to large‐sized native mammals (>1 kg) across the Atlantic Forest. We compiled data from 5380 ground‐level camera trap deployments in 3046 locations, from 2004 to 2020, resulting in 43,068 records of 58 species. These data add to existing data sets of mammals in the Atlantic Forest by including dates of camera operation needed for analyses dealing with imperfect detection. We also included, when available, information on important predictors of detection, namely the camera brand and model, use of bait, and obstruction of camera viewshed that can be measured from example pictures at each camera location. Besides its application in studies on the patterns and mechanisms behind occupancy, relative abundance, richness, and detection, the data set presented here can be used to study species' daily activity patterns, activity levels, and spatiotemporal interactions between species. Moreover, data can be used combined with other data sources in the multiple and expanding uses of integrated population modeling. An R script is available to view summaries of the data set. We expect that this data set will be used to advance the knowledge of mammal assemblages and to inform evidence‐based solutions for the conservation of the Atlantic Forest. The data are not copyright restricted; please cite this paper when using the data.

Genomic characterization of a highly divergent tomato chlorotic mottle Guyane virus strain in the Brazilian Amazon River Basin - Izaías Araújo de Oliveira; Luciane de Nazaré Almeida dos Reis; Flávia Milene Barros Nery; Niday Alline Nunes Fernandes; Vinícius Peres Machado Reis Gonçalves; Maria R. Rojas; Robert L. Gilbertson; Ailton Reis; Leonardo Silva Boiteux; Maria Esther de Noronha Fonseca-Boiteux; Rita de Cássia Pereira-Carvalho (Phytoparasitica, 2024)

How natural and anthropogenic factors should drive microplastic behavior and fate: The scenario of Brazilian urban freshwater - Fernando F. Sodré; Imisi M. Arowojolu; Maria C. Canela; Rodrigo S. Ferreira; Andreia N. Fernandes; Cassiana C. Montagner; Cristiane Vidal; Mariana A. Dias; Gilberto Abate; Leticia C. da Silva; Marco T. Grassi; Crislaine Bertoldi; et al. (Chemosphere, 2023)

Characterization of polysaccharides from a new variety of Stevia rebaudiana - Maria Rosa T. Zorzenon; Lorena G.B. Aristides; Cynthia Leticia S. Cabeça; Wellington F. dos Santos; Giuliana C.C. Grande; Laiza B. Beltran; Cecília E. Mareze-Costa; Antonio S. Dacome; Paula G.M. Fernandes; Thales R. Cipriani; Silvio Claudio da Costa (Bioactive Carbohydrates and Dietary Fibre, 2023)

Similar regional-scale survival of tropical and southern temperate birds from the New World - Leonardo Fernandes França; Clarisse Caroline de Oliveira e Silva; João Batista de Pinho; Nêmora Pauletti Prestes; Victor R. Cueto; Maria Alice S. Alves; Fabio Schunck; Carla Suertegaray Fontana; Camile Lugarini; Jaime Martinez; M. Cecilia Sagario; Javier Lopez de Casenave; et al. (Oecologia, 2023)

TRPV1 inactivation alters core body temperature and serum corticosterone levels: Impacts on clock genes expression in the liver and adrenal glands - Nayara AC. Horta; Paola Fernandes; Thais SR. Cardoso; Frederico SM. Machado; Lucas R. Drummond; Cândido C. Coimbra; Samuel P. Wanner; Ana Maria L Castrucci; Maristela O. Poletini (Journal of Thermal Biology, 2023)

Relationships between fluid mixing, biodiversity, and chemosynthetic primary productivity in Yellowstone hot springs - Maria C. Fernandes‐Martins; Daniel R. Colman; Eric S. Boyd (Environmental Microbiology, 2023)
The factors that influence biodiversity and productivity of hydrothermal ecosystems are not well understood. Here we investigate the relationship between fluid mixing, biodiversity, and chemosynthetic primary productivity in three co‐localized hot springs (RSW, RSN, and RSE) in Yellowstone National Park that have different geochemistry. All three springs are sourced by reduced hydrothermal fluid, but RSE and RSN receive input of vapour phase gas and oxidized groundwaters, with input of both being substantially higher in RSN. Metagenomic sequencing revealed that communities in RSN were more biodiverse than those of RSE and RSW in all dimensions evaluated. Microcosm activity assays indicate that rates of dissolved inorganic carbon (DIC) uptake were also higher in RSN than in RSE and RSW. Together, these results suggest that increased mixing of reduced volcanic fluid with oxidized fluids generates additional niche space capable of supporting increasingly biodiverse communities that are more productive. These results provide insight into the factors that generate and maintain chemosynthetic biodiversity in hydrothermal systems and that influence the distribution, abundance, and diversity of microbial life in communities supported by chemosynthesis. These factors may also extend to other ecosystems not supported by photosynthesis, including the vast subterranean biosphere and biospheres beneath ice sheets and glaciers.

Chironomus sancticaroli (Diptera: Chironomidae) in ecotoxicology: laboratory cultures and tests - Emília Marques Brovini; Haroldo Lobo; Raquel Fernandes Mendonça; Clarice Maria R. Botta; Ana Luiza Rangel Linhares Lima; Beatriz Corrêa Thomé de Deus; Simone Jaqueline Cardoso (Ecotoxicology, 2023)

Rock n' Seeds: A database of seed functional traits and germination experiments from Brazilian rock outcrop vegetation - Carlos A. Ordóñez‐Parra; Roberta L. C. Dayrell; Daniel Negreiros; Antônio C. S. Andrade; Letícia G. Andrade; Yasmine Antonini; Leilane C. Barreto; Fernanda de V. Barros; Vanessa da Cruz Carvalho; Blanca Auxiliadora Dugarte Corredor; Antônio Cláudio Davide; Alexandre A. Duarte; et al. (Ecology, 2023)
Advancing functional ecology depends fundamentally on the availability of data on reproductive traits, including those from tropical plants, which have been historically underrepresented in global trait databases. Although some valuable databases have been created recently, they are mainly restricted to temperate areas and vegetative traits such as leaf and wood traits. Here, we present Rock n' Seeds, a database of seed functional traits and germination experiments from Brazilian rock outcrop vegetation, recognized as outstanding centers of diversity and endemism. Data were compiled through a systematic literature search, resulting in 103 publications from which seed functional traits were extracted. The database includes information on 16 functional traits for 383 taxa from 148 genera, 50 families, and 25 orders. These 16 traits include two dispersal, six production, four morphological, two biophysical, and two germination traits—the major axes of the seed ecological spectrum. The database also provides raw data for 48 germination experiments, for a total of 10,187 records for 281 taxa. Germination experiments in the database assessed the effect of a wide range of abiotic and biotic factors on germination and different dormancy‐breaking treatments. Notably, 8255 of these records include daily germination counts. This input will facilitate synthesizing germination data and using this database for a myriad of ecological questions. Given the variety of seed traits and the extensive germination information made available by this database, we expect it to be a valuable resource advancing comparative functional ecology and guiding seed‐based restoration and biodiversity conservation in tropical megadiverse ecosystems. There are no copyright restrictions on the data; please cite this paper when using the current data in publications; also the authors would appreciate notification of how the data are used in publications.

Where and How to Sample Phthorimaea operculella (Zeller) (Lepidoptera: Gelechiidae) in Solanum tuberosum - Flávia M. Alves; Alfredo H. R. Gonring; Maria E. de S. Fernandes; Cristina S. Bastos; Flávio Lemes Fernandes (Potato Research, 2022)

AMAZONIA CAMTRAP: A data set of mammal, bird, and reptile species recorded with camera traps in the Amazon forest - Ana Carolina Antunes; Anelise Montanarin; Diogo Maia Gräbin; Erison Carlos dos Santos Monteiro; Fernando Ferreira de Pinho; Guilherme Costa Alvarenga; Jorge Ahumada; Robert B. Wallace; Emiliano Esterci Ramalho; Adrian Paul Ashton Barnett; Alex Bager; Alexandre Martins Costa Lopes; et al. (Ecology, 2022)
The Amazon forest has the highest biodiversity on Earth. However, information on Amazonian vertebrate diversity is still deficient and scattered across the published, peer‐reviewed, and gray literature and in unpublished raw data. Camera traps are an effective non‐invasive method of surveying vertebrates, applicable to different scales of time and space. In this study, we organized and standardized camera trap records from different Amazon regions to compile the most extensive data set of inventories of mammal, bird, and reptile species ever assembled for the area. The complete data set comprises 154,123 records of 317 species (185 birds, 119 mammals, and 13 reptiles) gathered from surveys from the Amazonian portion of eight countries (Brazil, Bolivia, Colombia, Ecuador, French Guiana, Peru, Suriname, and Venezuela). The most frequently recorded species per taxa were: mammals: Cuniculus paca (11,907 records); birds: Pauxi tuberosa (3713 records); and reptiles: Tupinambis teguixin (716 records). The information detailed in this data paper opens up opportunities for new ecological studies at different spatial and temporal scales, allowing for a more accurate evaluation of the effects of habitat loss, fragmentation, climate change, and other human‐mediated defaunation processes in one of the most important and threatened tropical environments in the world. The data set is not copyright restricted; please cite this data paper when using its data in publications and we also request that researchers and educators inform us of how they are using these data.

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Variants in GCNA, X-linked germ-cell genome integrity gene, identified in men with primary spermatogenic failure - Jimmaline J. Hardy; Margot J. Wyrwoll; William Mcfadden; Agnieszka Malcher; Nadja Rotte; Nijole C. Pollock; Sarah Munyoki; Maria V. Veroli; Brendan J. Houston; Miguel J. Xavier; Laura Kasak; Margus Punab; et al. (Human Genetics, 2021)

The use of denaturing solution as collection and transport media to improve SARS-CoV-2 RNA detection and reduce infection of laboratory personnel - Alex F. Carvalho; Raissa P. Rocha; Andreza P. Gonçalves; Thaís B. S. Silva; Hugo I. Sato; Larissa Vuitika; Flavia F. Bagno; Sarah A. R. Sérgio; Maria M. Figueiredo; Ronaldo B. Martins; Juliano P. Souza; Eurico Arruda; et al. (Brazilian Journal of Microbiology, 2021)

Photocatalytic degradation of acetaminophen and caffeine using magnetite–hematite combined nanoparticles: kinetics and mechanisms - Tiago A. Fernandes; Sofia G. Mendo; Liliana P. Ferreira; Nuno R. Neng; M. Conceição Oliveira; Adrià Gil; Maria Deus Carvalho; Olinda C. Monteiro; José M. F. Nogueira; Maria José Calhorda (Environmental Science and Pollution Research, 2021)

Chemical composition and larvicidal activity of the essential oil from the leaves of Onychopetalum periquino (Rusby) D.M. Johnson & N.A. Murray - Bruna R. de Lima; Felipe M. A. da Silva; Elzalina R. Soares; Richardson A. de Almeida; Jessica B. Maciel; Carromberth C. Fernandes; André C. de Oliveira; Wanderli P. Tadei; Hector H. F. Koolen; Afonso D. L. de Souza; Maria L. B. Pinheiro (Natural Product Research, 2021)

Microclimate and soil and water loss in shaded and unshaded agroforestry coffee systems - Anôr Fiorini de Carvalho; Elpídio Inácio Fernandes-Filho; Mayara Daher; Lucas de Carvalho Gomes; Irene Maria Cardoso; Raphael Bragança Alves Fernandes; Carlos E. G. R. Schaefer (Agroforestry Systems, 2021)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Bacillus thuringiensis endotoxin production: a systematic review of the past 10 years - José Manoel W. Duarte Neto; Maria Carolina de A. Wanderley; Túlio Alexandre F. da Silva; Daniela A. Viana Marques; Gilvanda R. da Silva; Josimar Fernandes Gurgel; José de Paula Oliveira; Ana Lúcia F. Porto (World Journal of Microbiology and Biotechnology, 2020)

Proteomic and phosphoproteomic analyses reveal several events involved in the early stages of bovine herpesvirus 1 infection - Marcos J. Magalhães-Junior; Maria Cristina Baracat-Pereira; Lorena K. J. Pereira; Camilo E. Vital; Marcus R. Santos; Pricila S. Cunha; Kenner M. Fernandes; Gustavo C. Bressan; Juliana L. R. Fietto; Abelardo Silva-Júnior; Márcia R. Almeida (Archives of Virology, 2020)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

ATLANTIC ‐ PRIMATES : a dataset of communities and occurrences of primates in the Atlantic Forests of South America - Laurence Culot; Lucas Augusto Pereira; Ilaria Agostini; Marco Antônio Barreto de Almeida; Rafael Souza Cruz Alves; Izar Aximoff; Alex Bager; María Celia Baldovino; Thiago Ribas Bella; Júlio César Bicca‐Marques; Caryne Braga; Carlos Rodrigo Brocardo; et al. (Ecology, 2019)
Primates play an important role in ecosystem functioning and offer critical insights into human evolution, biology, behavior, and emerging infectious diseases. There are 26 primate species in the Atlantic Forests of South America, 19 of them endemic. We compiled a dataset of 5,472 georeferenced locations of 26 native and 1 introduced primate species, as hybrids in the genera Callithrix and Alouatta . The dataset includes 700 primate communities, 8,121 single species occurrences and 714 estimates of primate population sizes, covering most natural forest types of the tropical and subtropical Atlantic Forest of Brazil, Paraguay and Argentina and some other biomes. On average, primate communities of the Atlantic Forest harbor 2 ± 1 species (range = 1–6). However, about 40% of primate communities contain only one species. Alouatta guariba (N = 2,188 records) and Sapajus nigritus (N = 1,127) were the species with the most records. Callicebus barbarabrownae (N = 35), Leontopithecus caissara (N = 38), and Sapajus libidinosus (N = 41) were the species with the least records. Recorded primate densities varied from 0.004 individuals/km 2 ( Alouatta guariba at Fragmento do Bugre, Paraná, Brazil) to 400 individuals/km 2 ( Alouatta caraya in Santiago, Rio Grande do Sul, Brazil). Our dataset reflects disparity between the numerous primate census conducted in the Atlantic Forest, in contrast to the scarcity of estimates of population sizes and densities. With these data, researchers can develop different macroecological and regional level studies, focusing on communities, populations, species co‐occurrence and distribution patterns. Moreover, the data can also be used to assess the consequences of fragmentation, defaunation, and disease outbreaks on different ecological processes, such as trophic cascades, species invasion or extinction, and community dynamics. There are no copyright restrictions. Please cite this Data Paper when the data are used in publications. We also request that researchers and teachers inform us of how they are using the data.

Understanding Conformational Dynamics of Complex Lipid Mixtures Relevant to Biology - Ran Friedman; Syma Khalid; Camilo Aponte-Santamaría; Elena Arutyunova; Marlon Becker; Kevin J. Boyd; Mikkel Christensen; João T. S. Coimbra; Simona Concilio; Csaba Daday; Floris J. van Eerden; Pedro A. Fernandes; et al. (The Journal of Membrane Biology, 2018)

Tissue residue depletion of moxidectin in lambs ( Ovis aries ) following subcutaneous administration - Michelle Del Bianchi A. Cruz; Maria Ângela M. Fernandes; Alda Lúcia G. Monteiro; Juliana A. Teles; Arturo Anadón; Felix G. R. Reyes (Food Additives & Contaminants: Part A, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Intralesional uridine-5′-triphosphate (UTP) treatment induced resistance to Leishmania amazonensis infection by boosting Th1 immune responses and reactive oxygen species production - Camila Marques-da-Silva; Mariana M. Chaves; Maria Luiza Thorstenberg; Vanessa R. Figliuolo; Flávia S. Vieira; Suzana P. Chaves; José Roberto Meyer-Fernandes; Bartira Rossi-Bergmann; Luiz Eduardo Baggio Savio; Robson Coutinho-Silva (Purinergic Signalling, 2018)

Advances on the molecular characterization, clinical relevance, and detection methods of Gadiform parvalbumin allergens - Telmo J. R. Fernandes; Joana Costa; Isabel Carrapatoso; Maria Beatriz P. P. Oliveira; Isabel Mafra (Critical Reviews in Food Science and Nutrition, 2017)

Standardization and Prevalence of the Booster Phenomenon: Evaluation Using a Two-Step Skin Test with 43 kDa Glycoprotein in Individuals from an Endemic Region of Paracoccidioidomycosis - Ana Paula C. Marques; Sandra Maria V. L. Oliveira; Grazielli R. Rezende; Dayane A. Melo; Sonia M. Fernandes-Fitts; Elenir Rose J. C. Pontes; Maria da Glória Bonecini-Almeida; Zoilo P. Camargo; Rinaldo P. Mendes; Anamaria M. M. Paniago (Mycopathologia, 2017)

Genetic background of novel sequence types of CTX-M-8- and CTX-M-15-producing Escherichia coli and Klebsiella pneumoniae from public wastewater treatment plants in São Paulo, Brazil - Milena Dropa; Nilton Lincopan; Livia C. Balsalobre; Danielle E. Oliveira; Rodrigo A. Moura; Miriam Rodriguez Fernandes; Quézia Moura da Silva; Glavur R. Matté; Maria I. Z. Sato; Maria H. Matté (Environmental Science and Pollution Research, 2016)

Evaluation of flavonols and derivatives as human cathepsin B inhibitor - Suelem D. Ramalho; Lorena R. F. de Sousa; Marcela C. M. Burger; Maria Inês S. Lima; M. Fátima das G. F. da Silva; João B. Fernandes; Paulo C. Vieira (Natural Product Research, 2015)

Molecular detection and phylogenetic analysis of bovine astrovirus in Brazil - Marcelo Candido; Anna Luiza Farias Alencar; Sabrina R. Almeida-Queiroz; Maria da Glória Buzinaro; Flavia Simone Munin; Silvia Helena Seraphin de Godoy; Marcia Cristina Livonesi; Andrezza Maria Fernandes; Ricardo Luiz Moro de Sousa (Archives of Virology, 2015)

3-Indol carboxaldehyde, an imidazole synthesized from naphthoquinone β-lapachone downregulates Candida albicans biofilm - José Alexandre da Rocha Curvelo; Anna Lea Silva Barreto; Camila A. dos Anjos; Rafaela S. Santana; Ariadne Nunes Alonso; Maria Teresa Vilela Romanos; Kelly C. G. de Moura; Paula Fernandes Carneiro; Maristela Barbosa Portela; Maria do Carmo F. R. Pinto; Rosangela Maria de Araújo Soares (Medicinal Chemistry Research, 2015)

Mild Thiamine Deficiency and Chronic Ethanol Consumption Modulate Acetylcholinesterase Activity Change and Spatial Memory Performance in a Water Maze Task - Ieda de Fátima Oliveira-Silva; Silvia R. Castanheira Pereira; Paula A. Fernandes; Andrea F. Ribeiro; Rita G. W. Pires; Angela Maria Ribeiro (Journal of Molecular Neuroscience, 2015)

Phthaloyl amino acids as anti-inflammatory and immunomodulatory prototypes - Ana Cristina Lima Leite; Fábio Fernandes Barbosa; Marcos Veríssimo de Oliveira Cardoso; Diogo R. M. Moreira; Lucas Cunha D. Coêlho; Elany Barbosa da Silva; Gevanio Bezerra de Oliveira Filho; Valdênia Maria Oliveira de Souza; Valéria Rêgo A. Pereira; Luiza de C. Reis; Paulo Michel Pinheiro Ferreira; Claudia Pessoa; et al. (Medicinal Chemistry Research, 2014)

Evaluation of Paracoccidioides brasiliensis Infection by gp 43 Intradermal Test in Rural Settlements in Central-West Brazil - Ana Paula da C. Marques; Sandra Maria V. L. Oliveira; Grazielli R. Rezende; Dayane A. Melo; Sonia M. Fernandes-Fitts; Elenir Rose J. C. Pontes; Maria da Glória Bonecini-Almeida; Zoilo P. Camargo; Anamaria M. M. Paniago (Mycopathologia, 2013)

−1131T>C and SW19 polymorphisms in APOA5 gene and lipid levels in type 2 diabetic patients - Mirelle O. Sóter; Karina B. Gomes; Ana P. Fernandes; Maria das G. Carvalho; Poliana S. Pinheiro; Adriana A. Bosco; Daniel D. R. Silva; Marinez O. Sousa (Molecular Biology Reports, 2012)

HFE, MTHFR, and FGFR4 genes polymorphisms and breast cancer in Brazilian women - Anna P. Batschauer; Nathalia G. Cruz; Vanessa C. Oliveira; Fernanda F. Coelho; Izabela R. Santos; Michelle T. Alves; Ana P. Fernandes; Maria G. Carvalho; Karina B. Gomes (Molecular and Cellular Biochemistry, 2011)

Mutations in methylenetetrahydrofolate reductase and in cysthationine beta synthase: is there a link to homocysteine levels in peripheral arterial disease? - Maria E. R. C. Santos; Francisco das C. L. e Silva; Karina B. Gomes; Ana Paula M. Fernandes; Fernanda R. Freitas; Mayara C. Faria; Ana Paula L. Mota; Maria G. Carvalho (Molecular Biology Reports, 2011)

Antidepressant-like effects of Trichilia catigua (Catuaba) extract: evidence for dopaminergic-mediated mechanisms - Maria M. Campos; Elizabeth S. Fernandes; Juliano Ferreira; Adair R. S. Santos; João B. Calixto (Psychopharmacology, 2005)